Respostas

2013-07-02T22:49:07-03:00

A) (x+5)² = (x+5).(x+5) = x² + 5x + 5x + 25 = x² + 10x + 25

B) (x+y)² = (x+y).(x+y) = x² + xy + xy + y² = x² + 2xy + y²

C) (3x+2)² = (3x+2).(3x+2) = 9x² + 6x + 6x + 4= 9x² + 12x + 4

D) (x-7)² = (x-7).(x-7) =  x² - 7x - 7x + 49 = x² - 14x + 49

E) (2x-5)² = (2x-5).(2x-5) = 4x² - 10x - 10x + 25 = 4x² - 20x + 25

F) (3x-2).(3x+2) = 9x² + 6x - 6x - 4 = 9x² - 4

G) (5x+4).(5x-4) = 25x² - 20x + 20x - 16 = 25x² - 16

H) (3x+y).(3x-y) = 9x² - 3xy + 3xy - y² = 9x² - y²

 

espero ter te ajudado

 

2 5 2
2013-07-03T02:32:57-03:00

a) (x+5)² = (x+5).(x+5) = x² + 5x + 5x + 25 = x² + 10x + 25

b) (x+y)² = (x+y).(x+y) = x² + xy + xy + y² = x² + 2xy + y²

c) (3x+2)² = (3x+2).(3x+2) = 9x² + 6x + 6x + 4= 9x² + 12x + 4

d) (x-7)² = (x-7).(x-7) =  x² - 7x - 7x + 49 = x² - 14x + 49

e) (2x-5)² = (2x-5).(2x-5) = 4x² - 10x - 10x + 25 = 4x² - 20x + 25

f) (3x-2).(3x+2) = 9x² + 6x - 6x - 4 = 9x² - 4

g) (5x+4).(5x-4) = 25x² - 20x + 20x - 16 = 25x² - 16

h) (3x+y).(3x-y) = 9x² - 3xy + 3xy - y² = 9x² - y²

1 4 1